A hydrogen peroxide biosensor from horseradish peroxidase immobilization onto acrylic microspheres - Eda Yuhana Ariffin,; Nik Nurhanan Nik Mansor,; Safitri, Eka; Lee, Yook Heng; Nurul Izzaty Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The sensitive and rapid detection of hydrogen peroxide is very important in the areas of clinical and environmental analyses. A sensitive and selective Horseradish peroxidase (HRP)-hydrogen peroxide (H2O2) biosensor was developed based on acrylic microspheres. Hydrophobic poly(n-butyl acrylate-N-acryloxysuccinimide) [poly(nBA-NAS)] microspheres were synthesized using photopolymerization in an emulsion to form an enzyme immobilization matrix. The HRP enzyme was covalently immobilized onto the acrylic microspheres via the succinimide functionality. Field emission scanning electron microscope (FESEM) has been utilized to characterize the screen-printed carbon paste electrode (SPE) constructed from enzyme conjugated acrylic microspheres and gold nanoparticles (AuNPs) composite (HRP/nBA-NAS/AuNPs/SPE). Differential pulse voltammetry was used to assess the biosensor performance. The linear response range of the hydrogen peroxide biosensor obtained was from 1.0 × 10-2 to 1.0 × 10-10 M (R2 = 0.99) with the limit of detection (LOD) approximately at 1.0 × 10-10 M. This is an improvement over many hydrogen peroxide biosensors reported so far. Such improvement may be attributed to the large surface area provided by the acrylic microspheres as a matrix for immobilization of the HRP enzyme.